1991
DOI: 10.1128/aem.57.7.1899-1904.1991
|View full text |Cite
|
Sign up to set email alerts
|

Processing of the lactococcal extracellular serine proteinase

Abstract: Activity of the lactococcal cell envelope-located serine proteinase depends on the presence of membraneassociated lipoprotein PrtM. To differentiate between the action of the proteinase and the action of PrtM in the process of proteinase maturation, an inactive form of the lactococcal proteinase was constructed. This was done by mutating one of the three amino acids thought to constitute the active site of the enzyme. The secreted form of this inactivated proteinase was the same size as the inactive secreted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…In other words, free a S1 -casein could be less susceptible to the action of proteinase than when it is in a complex with other casein fractions. Release of lactococcal proteinase from the cell envelope was found to be an autoproteolytic event (Laan and Konings 1989;Haandrikman et al 1991). It was also found that Ca 2+ ions play an important role in maintaining the attachment of the enzyme to the cell.…”
Section: Discussionmentioning
confidence: 97%
“…In other words, free a S1 -casein could be less susceptible to the action of proteinase than when it is in a complex with other casein fractions. Release of lactococcal proteinase from the cell envelope was found to be an autoproteolytic event (Laan and Konings 1989;Haandrikman et al 1991). It was also found that Ca 2+ ions play an important role in maintaining the attachment of the enzyme to the cell.…”
Section: Discussionmentioning
confidence: 97%
“…200 kDa), which involves removal of an N-terminal signal sequence of 33 amino acid residues and a 154-residue pro-sequence [32,34,35], results in a mature proteinasc of approximately 180 kDa. The product of a second closely linked gene (prtM) encoding a membrane-bound lipoprotein is also essential for maturation of the proteinase [33,36,37]. Most of what we know about the action of the cell envelope proteinase from lactococci in hydrolysing milk proteins has been learnt from studies of the enzyme after its release from the cell.…”
Section: The Cell Ent'elope Proteinasementioning
confidence: 99%
“…The other mechanism [42] involves an autoproteolytic cleavage at a site close to the C-terminal wall-associated sequence occurring as a result of a conformational change induced by the removal of calcium. Recent studies [36,43], in which release of the proteinase was monitored by a monoclonal antibody ELISA assay, provide compelling evidence for the involvement of an autoproteolytic event in release. Release was prevented (even in the presence of EDTA) by treatment with proteinase inhibitors [43] or by abolishing proteolytic activity by site-directed mutagenesis of a single active site residue [36].…”
Section: Nature Of the Proteinase Release Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…One should bear in mind that PrtP is being activated through the autoproteolytic removal of the N-terminal pro-region, during the maturation process. In addition, active enzymes are prone to additional auto-digestion, especially when no Ca 2+ ions are present to stabilize the enzyme on the cell surface (24). Finally, PrtP is capable of hydrolyzing autolysin AcmA, a protein responsible for cell separation and autolysis during the stationary phase of growth (25), as well as some extracellular proteins of unknown function (24).…”
Section: Discussionmentioning
confidence: 99%